2022
DOI: 10.24018/clinicmed.2022.3.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Omicron Variant (B.1.1.529) of SARS-CoV-2, A Worldwide Public Health Emergency!

Abstract: B.1.1.529 is the newest form of SARS- CoV-2. It was initially reported to the World Health Organization (WHO) on November 24, 2021, by South Africa. WHO recognized it as a variant of concern on November 26, 2021, and named it "Omicron.” The Omicron variant features an exceptionally large number of mutations, many of which are unique, and a substantial number of which impair the spike protein targeted by most COVID-19 vaccines at the time of its discovery. Despite initial studies showing that the variant caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Zeng et al (2021) reported that Omicron has a significantly enhanced efficiency of cell-to-cell transmission, with 4.8-fold higher levels than D614G and other variants [183]. On 8 November 2021, this variant was discovered in South Africa, and within two weeks, more than 70% of sequenced samples from Gauteng province in South Africa were Omicron [299]. By 11 December 2021, the United States had reported that the Omicron variant was responsible for nearly 7% of COVID cases.…”
Section: Transmissibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Zeng et al (2021) reported that Omicron has a significantly enhanced efficiency of cell-to-cell transmission, with 4.8-fold higher levels than D614G and other variants [183]. On 8 November 2021, this variant was discovered in South Africa, and within two weeks, more than 70% of sequenced samples from Gauteng province in South Africa were Omicron [299]. By 11 December 2021, the United States had reported that the Omicron variant was responsible for nearly 7% of COVID cases.…”
Section: Transmissibilitymentioning
confidence: 99%
“…In the next two weeks, this rate quickly increased to around 23% and 60%, respectively [300]. The variant has now been identified in all 50 states and became the dominant variant within just three weeks since its discovery in the United States [299]. On 4 January 2022, the United States alone recorded more than one million cases [301].…”
Section: Transmissibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The Omicron variant is unique in that it contains the most mutations of all SARS-CoV-2 variants ( Figure 4 ). A total of 50 mutations have occurred in this variant [ 66 ]. The envelope (E) protein has one substitution (T9I), the membrane (M) protein has three substitutions (D3G, Q19E, and A63T), and the nucleocapsid (N) protein has three substitutions and a three-residue deletion.…”
Section: Omicron Variant and Its Characteristicsmentioning
confidence: 99%